Population structure of Uncancylus concentricus (d'Orbigny, 1835) (Ancylidae, Pulmonata, Basommatophora) in the Multiple Use Reserve Martín García Island, Upper Río de la Plata, Argentina - Martin, Stella Maris (2012)
The present work analyzes the population dynamics of Uncancylus concentricus in natural conditions in the northeastern coastal area of the Multiple Use Natural Reserve Isla Martín García (Beach of Basural), Buenos Aires, Argentina. Martín García Island is located in the Upper Río de La Plata, to the south of the mouth of the Uruguay River (34° 11' 25" S and 58° 15'38" W). Monthly collections were made from August 2005 to December 2006. The size frequency of the U. concentricus population throughout the sampling period ranges from 1.2 to 8.3 m. The changes in the size frequencies throughout the months surveyed indicate a variable distribution pattern because of the increase and decrease in water flow, but we observed a peak in the frequency of individuals within the size range 3.5 to 4.5 mm in the population. It can be concluded that this species lives for at least a year in the wild since the juveniles are highly abundant in spring and summer.